Aqueous Environmental Geochemistry - Langmuir, Donald
Langmuir provides a thorough presentation of natural chemical concentrations, systems and processes to help readers (1) understand controls on the chemical quality of surface and subsurface waters, and (2) distinguish between the natural and the anthropogenic. Unlike most authors, whose civil/sanitary engineering backgrounds promote a more aquatic chemistry perspective, LangmuirÕs geology/geochemistry experience focuses coverage on the chemical interactions between water and geological materials. The book provides valuable training in using in the geochemical computer code MINTEQA2 as an integral problem-solving tool